Análise filogenética da beta-caseína de diferentes espécies de produção animal - análise in sílico (national center for biotechnology information) - Barros, Rinara Conceição Cruz (Brasil, 2024)
This work aims to carry out an in silicon study of the evolutionary process of Beta-casein genes within the main species of animal production and Homo sapiens, in order to establish an evolutionary hypothesis of the Beta-casein gene, through a dendrogram with molecular genetic data. Initially, a survey of the genomic sequences of the CSN2 gene, which encodes the beta-casein protein, found in the National Center for Biotechnology Information (NCBI) database, of the respective species was carried out: Cattle (Bos taurus taurus and Bos taurus indicus), buffalo (Bubalus bubalis), goat (Capra hircus), sheep (Ovis aries) and the human species (Homo sapiens). Subsequently, the applied methodology turned to the multiple alignment of the genomic sequences of the gene studied, through the Clustal X program version 1.83, then with the aid of the NJPLOT Wind 95 program it was possible to obtain the dendrogram of the groups of the species. With the results obtained, it was possible to verify that the species Bos taurus taurus, Bos taurus indicus and Bubalus bubalis presented high genetic similarity for beta-casein, and there was a distancing for the species Homo sapiens. The goat and sheep species were also subdivided to form a group, indicating genetic similarity to the gene under study. These results provide a better understanding of the evolutionary processes between species with the genes of the proteins present in milk, it is possible to distinguish the forms of beta-casein and understand its molecular structure, in addition to generating subsidies for improvements in the development of technologies, increases the potential of the bioinformatics tool, in order to help in the studies of evolution, animal breeding and conservation of genetic resources.